Evidence for a Role of rpoE in Stressed and Unstressed Cells of Marine Vibrio angustum Strain S14 - Hild, Erika (American Society for Microbiology, 2000)
We report the cloning, sequencing, and characterization of the rpoE homolog in Vibrio angustum S14. The rpoE gene encodes a protein with a predicted molecular mass of 19.4 kDa and has been demonstrated to be present as a single-copy gene by Southern blot analysis. The deduced amino acid sequence of RpoE is most similar to that of the RpoE homolog of Sphingomonas aromaticivorans, ς(24), displaying sequence similarity and identity of 63 and 43%, respectively. Northern blot analysis demonstrated the induction of rpoE 6, 12, and 40 min after a temperature shift to 40°C. An rpoE mutant was constructed by gene disruption. There was no difference in viability during logarithmic growth, stationary phase, or carbon starvation between the wild type and the rpoE mutant strain. In contrast, survival of the mutant was impaired following heat shock during exponential growth, as well as after oxidative stress at 24 h of carbon starvation. The mutant exhibited microcolony formation during optimal growth temperatures (22 to 30°C), and cell area measurements revealed an increase in cell volume of the mutant during growth at 30°C, compared to the wild-type strain. Moreover, outer membrane and periplasmic space protein analysis demonstrated many alterations in the protein profiles for the mutant during growth and carbon starvation, as well as following oxidative stress, in comparison with the wild-type strain. It is thereby concluded that RpoE has an extracytoplasmic function and mediates a range of specific responses in stressed as well as unstressed cells of V. angustum S14.